MIND THE FILM: PHOTOGRAPHS AND FILMS WITH LOST NARRATIVES. - Peraica, Ana (Afterimage)
The essay examines the limitations of documentary films and photographs of war using the concepts of socialistic ideology. The author believes that all historical documents, especially master narratives, should be approached with skepticism to determine if they have been subject to manipulation and forgery. The essay focuses on two pictures of Yugoslavian Bishop Aloysius Stepinac in Zagreb with Croatian leader Vladimir Bakaric.